The Relevance of Imam al-Māwardī’s Thought to the Legislative Process of Aceh’s Qanun by the Aceh People's Representative Council - Lubis, Gusni; Melayu, Hasnul Arifin; Jihad, Azka Amalia (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The process of legislation on the Qanun by the Aceh People's Representative Council (DPRA) is a unique legal mechanism in the Indonesian government system, because it is closely related to the implementation of Islamic sharia in Aceh. This study aims to see the relevance of the Qanun legislation process in Aceh from the perspective of the concept of Islamic politics put forward by Imam Al-Mawardi, a classical Islamic thinker who discusses a lot of Islamic government theory and law. This research uses a qualitative approach with descriptive analysis methods and literature studies on Al-Mawardi's thoughts in the book Al-Ahkam As-Sultaniyyah. The results of the study show that in the Qanun legislation process, the DPRA plays a role as a legislative body that has the authority to formulate regional regulations based on Islamic law. However, in practice, there are still challenges such as local political dynamics, the interests of various actors, and synchronization with national law. So, how does the DPRA use the concept of Islam in the Qanonic legislation process? And in the legislative process, the DPRA prioritizes certain political interests over the interests of the people? Al-Mawardi's perspective provides insight that good legislation must pay attention to the balance between Islamic law and the benefit of the ummah, and avoid political interests that can hinder the ideal implementation of sharia. Thus, this research contributes to the understanding of the Qanun legislation process from an Islamic political perspective and offers recommendations so that the DPRA can carry out its duties more optimally following the principles of ideal Islamic governance according to Al-Mawardi.